2019
DOI: 10.9734/aprj/2019/v3i230061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Doses of Urea on the Yield of Boro Rice Varieties in Haor Areas of Bangladesh

Abstract: The experiment was carried out at Sunamganj district during November 2016 to May 2017 to observed the effect of urea fertilizer on the yield of boro rice varieties in haor areas of Bangladesh. Two factors experiment viz. Varieties BRRI dhan29 and BRRI dhan58; and six urea fertilizer levels including: 340 (F1), 320 (F2), 300 (F3), 280 (F4), 260 (F5), and 165 kg ha-1 (F6) [Farmer’s practice (FP)] were used. In case of F1-F5, the MoP-TSP-CaS04-ZnS04 as 127-112-75-11 kg ha-1 were used while Farmers’ practice (FP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
5
2
0
1
Order By: Relevance
“…The lower number of tillers hill -1 (7.39, 10.66 and 11.85 at 30, 60 DAT and at harvest, respectively) was found from the treatment N 3 which was statistically identical with N 1 . More or less similar result was also observed by Karim (2019), Adhikari (2018) and Chamely and Islam (2015) also found that N had significant effect on number of tillers hill -1 . The maximum number of tillers hill -1 (11.43, 16.17 and 16.40 at 30, 60 DAT and at harvest, respectively) was found from the treatment combination of D 2 N 2 which was statistically similar with the treatment combination of D 1 N 1 , D 1 N 2 , D 2 N 1 and D 3 N 2 .…”
Section: Number Of Tillers Hill -1supporting
confidence: 83%
See 1 more Smart Citation
“…The lower number of tillers hill -1 (7.39, 10.66 and 11.85 at 30, 60 DAT and at harvest, respectively) was found from the treatment N 3 which was statistically identical with N 1 . More or less similar result was also observed by Karim (2019), Adhikari (2018) and Chamely and Islam (2015) also found that N had significant effect on number of tillers hill -1 . The maximum number of tillers hill -1 (11.43, 16.17 and 16.40 at 30, 60 DAT and at harvest, respectively) was found from the treatment combination of D 2 N 2 which was statistically similar with the treatment combination of D 1 N 1 , D 1 N 2 , D 2 N 1 and D 3 N 2 .…”
Section: Number Of Tillers Hill -1supporting
confidence: 83%
“…The highest number of noneffective tillers hill -1 (3.45) was found from the treatment N 3 while lower number of non-effective tillers hill -1 (2.26) was found from the treatment N 2 followed by N 1 . The result obtained from the present study was followed with the findings of Karim (2019) and Adhikari (2018). In treatment combinations, lower number of non-effective tillers hill -1 (1.40) was found from D 2 N 2 which was statistically similar with D 1 N 2 and D 2 N 1 .…”
Section: Number Of Non-effective Tillers Hill -1supporting
confidence: 72%
“…Patel et al (2019) concluded that, aged seedlings produce fewer tillers due to the reduction of vegetative period and thereby result in poor yield. Karim et al (2019) alluded that, mean effective tiller/hill of BRRI dhan58 was 12.30 with varietal effect. The present result is different from the earlier findings may be due to less variation in weather during the sowing intervals and it also may have happened due to soil fertility factor(s).…”
Section: Discussionmentioning
confidence: 92%
“…It is well known that nitrogen fertilizers significantly increase rice yields, especially since the development of current varieties. A significant component of protoplasm, protein, and chlorophyll is the nutrient nitrogen (Karim et al, 2019). The application of nitrogen fertilizer in an inefficient manner raises production costs and degrades product quality (Mahato et al, 2019).…”
Section: Original Research Articlementioning
confidence: 99%